2016
DOI: 10.1371/journal.pone.0147644
|View full text |Cite
|
Sign up to set email alerts
|

“Immunonutrition” Has Failed to Improve Peritonitis-Induced Septic Shock in Rodents

Abstract: BackgroundImmunonutrition in sepsis, including n-3 poly-unsaturated fatty acids (PUFAs) or L-arginine supplementation, is a controversial issue that has yielded a great number of studies for the last thirty-five years, and the conclusions regarding the quantity and quality of this support in patients are deceiving. The aim of the present experimental study is to investigate the effects of a pretreatment with enteral nutrition enriched with n-3 PUFAs or L-arginine on vascular dysfunctions, inflammation and oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…Similar negative results were observed in C. rodentium infected C57BL/6 mice consuming omega-3 polyunsaturated fatty acids from flaxseed [103]. Omega-3 polyunsaturated fatty acids similarly exacerbated peritonitis-induced septic shock in rats [104].…”
Section: Omega-3 Polyunsaturated Fatty Acidssupporting
confidence: 57%
“…Similar negative results were observed in C. rodentium infected C57BL/6 mice consuming omega-3 polyunsaturated fatty acids from flaxseed [103]. Omega-3 polyunsaturated fatty acids similarly exacerbated peritonitis-induced septic shock in rats [104].…”
Section: Omega-3 Polyunsaturated Fatty Acidssupporting
confidence: 57%
“…Some researchers have raised objections to this conclusion. The results from a recent study on rodents suggested that although n -3 polyunsaturated fatty acids had an antioxidant effect, they might worsen septic shock–induced vascular dysfunction, and not improve the survival rate of the disease [ 38 ]. The results from clinical trials had similar conclusions to these animal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, various lines of evidence suggest that nutritional support may not provide any benefit, and indeed, may potentially be harmful in certain contexts. In a rat model of septic shock, “immunonutrition” with polyunsaturated fatty acids or arginine aggravated disease progression [ 22 ]. Similarly, nutritional intervention has not consistently been demonstrated to be effective in critically ill patients.…”
Section: Is Nutritional Support Beneficial?mentioning
confidence: 99%